A study of remedies prescribed at Glasgow Homoeopathic Hospital - Kayne, Steven; Beattie, Neil (British Homeopathic Journal, 1998)
In order to determine prescribing trends, data on the numbers of homoeopathic prescriptions in a winter month in four years were collected at the Glasgow Homoeopathic Hospital. The level of experience of prescribing doctors were also calculated. The most commonly prescribed medicine was Natrum muriaticum, the most frequently used dilution was 200 c.
Keywords: Glasgow Homoeopathic Hospital; Prescribing trends; weighted experience factor; potencies; polychrests; SHoRT